Multi-Locus GWAS of Quality Traits in Bread Wheat: Mining More Candidate Genes and Possible Regulatory Network - Yang, Yang; Chai, Yongmao; Zhang, Xuan; Lu, Shan; Zhao, Zhangchen; Wei, Di; Chen, Liang; Hu, Yin-Gang (Frontiers in Plant Science, 2020)
The improvement of quality traits, including grain quality traits and dough rheological properties, are important goal in wheat breeding for a long time. To understand the genetic basis of key quality traits of wheat, two single-locus and five multi-locus GWAS models were performed for six grain quality traits and three dough rheological properties based on 19, 254 SNPs in 267 bread wheat accessions. As a result, 299 quantitative trait nucleotides (QTNs) within 105 regions were identified to be associated with these quality traits in four environments. Among the 105 QTN regions, 40 core QTN regions were stably detected in at least three environments, 19 of which are novel. Compared with the previous studies, these novel QTN regions explained smaller phenotypic variation, which verified the advantages of the multi-locus GWAS models in detecting important small effect QTNs associated with complex traits. After detailed function and expression analysis, 67 core candidate genes involved in protein/sugar synthesis, histone modification and transcription factor regulation were determined to be related to grain quality formation, which indicated that wheat grain quality was affected by multi-level regulation. Finally, a preliminary network of gene regulation that may affect wheat quality formation was inferred. This study verified the power and reliability of multi-locus GWAS methods in wheat quality trait research, and increased the understanding of wheat quality formation mechanisms. The detected QTN regions and candidate genes in this study could be further used for gene cloning and marker-assisted selection in high-quality breeding of bread wheat.